AUTOMASI PENGELOLAAN BEBAN KERJA DOSEN DI PERGURUAN TINGGI SWASTA (PTS) SECARA EFEKTIF DENGAN AI - Rizkabayu Aditya; M. Agus Salim (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to explore the potential utilization of Artificial Intelligence (AI) in managing the workload of lecturers at Private Higher Education Institutions (PTS). The background of this research stems from the high administrative, academic, and research workload faced by lecturers at PTS due to limited infrastructure and resources (Rakhmani & Siregar, 2016; Priyono, 2018). Using a mixed-methods approach, this research involved the distribution of pre-simulation (n = 47) and post-simulation (n = 48) questionnaires, along with interviews with 15 lecturers from three PTS. The AI implementation simulation focused on automated grading and class schedule management. The results of the study show a significant reduction in administrative workload from the